Rehospitalization in Infants Born < 29 Weeks' Gestation during the First 2 Years of Life: Risk Assessment - Taylor, Jane B.; Go, Mitzi A.; Nyp, Michael F.; Legino, Jennifer; Norberg, Michael; Dai, Hongying; Truog, William E. (American Journal of Perinatology, 2016)
Objective This study aims to determine risk factors for rehospitalization in extremely premature infants.Study Design A retrospective cohort study of 157 infants born < 29 weeks' gestational age assessing risk factors for rehospitalization through 2 years of life.Results Multivariable logistic regression showed that an increasing number of respiratory infections (odds ratio [OR]: 1.8 [1.1–3.1] per infection p = 0.03) and inhaled steroid use at 1 year (OR: 4.0 [1.3–12.1] p = 0.01) were predictive of hospital readmission. Diuretic (OR: 27 [1.01–1,000] p = 0.04) and oxygen (OR: 32 [3.1–333] p = 0.004) use at 1 year were predictive of pediatric intensive care unit admission. The number of respiratory infections (OR: 2.8 [1.7–4.5] p < 0.0001) with reflux/aspiration necessitating G-tube/Nissen fundoplication surgical intervention with or without G-tubes alone (OR: 21.3 [2.9–166.7] p = 0.02 and OR: 22.7 [CI, 2.4–200] p = 0.04) was predictive of increased number of rehospitalizations.Conclusions Key modifiable risk factors identified were reflux/aspiration and ongoing respiratory infections. Critical time periods for diuretic, oxygen, and inhaled steroid use in this population occurred at the age of 1 year.
Keywords: prematurity; rehospitalization; bronchopulmonary dysplasia; dysphagia; respiratory infection; pulmonary hypertension